COMBINATION SYNDROME: A LITERATURE REVIEW OF GENERAL ASPECTS AND TREATMENTS - Penitente, Paulo Augusto [UNESP]; Silva, Emily Vivianne Freitas da [UNESP]; Souza, João Paulo do Vale [UNESP]; Jorge, Caroline de Freitas [UNESP]; Bittencourt, Ana Beatriz Bueno Carlini [UNESP]; Santos, Daniela Micheline dos [UNESP]; Melo Neto, Clóvis Lamartine de Moraes [UNESP]; Goiato, Marcelo Coelho [UNESP] (Termedia Sp. z.o.o., 2022)
Introduction: Combination syndrome is characterized mainly by anterior bone atrophy of the edentulous maxilla of compressive enlargement of the area due to antagonist arch, causing an occlusal disharmony and thus, a deformity in the alveolar bone. Objectives: The aim of the review was to investigate the causes and types of treatments available in scientific literature. Material and methods: This literature review evaluated main clinical aspects and rehabilitative treatments for combination syndrome. PubMed and Scopus databases were used with studies published until May 2021. Clinical trials, randomized and non-randomized studies, classic and comparative investigations, multicenter and in-vivo studies, case reports, longitudinal studies, and literature reviews were all included in this review. Results: Various studies have shown that anterior maxilla atrophy is the most commonly seen clinical feature; however, other features of the syndrome have not been observed in any patient. In oral rehabilitation, the use of implants mainly in the posterior region of the mandible, ensured greater occlusal balance, new bone formation in the peri-implant region, and decreased excessive compression of the anterior region of the maxilla. Conclusions: Clinical evaluation of the causes that resulted in deformities between alveolar bones and rehabilitating these regions to offer a better distribution of forces and quality of life to patients is essential.
Keywords: combination syndrome; complete denture; removable partial denture